Calidad educativa - Espinaza Barba, Gertrudis (2010)
In today 's world there is much literature, as well as national and international congresses and study groups held on "educational quality", but what is the focus of these? These hold debate on education in school, on the teacher' s effkiency, in topics that have invaded society in the search for methods and means for intellectual efficiency. All of these are very interesting, necessary, and admirable. This article will address a subject that may be out of fashion forthe "modern people". Nevertheless, the basis seems to have been forgotten -the foundation from where all education and "educational quality" derives from. When entering into the world, the human being brings along great wealth in raw, something that God in its infinite kindness gives. In the beginning of a child's development, the parents obviously are the child's first educators and the privileged place for education is home. In this challenging world an education of authentic quality is required and therefore it must be an integral one. This quality will soundly form toda y' s children and adolescents, and will shape a happyfuture for tomorrow's men and women. Furthermore, there is room to address this issue in terms of education which is under the direct responsibility of the educator in the school.